Eye of the earthquake dragon - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters, 2019)
The evil wizard Maldred has stolen the gold and silver keys which will allow him to release the Naga, the powerful earthquake dragon at the center of the earth--so Drake and several of the other Dragon Masters travel to the Naga's Temple in the Dragon Islands, to try and stop Maldred, and prevent him and the earthquake dragon from destroying the kingdom.